1989
DOI: 10.1002/jat.2550090507
|View full text |Cite
|
Sign up to set email alerts
|

Transient renal impairment in rats after oral exposure to diethylene glycol

Abstract: Volume, specific gravity, creatinine, lactate dehydrogenase (LDH), leucine aminopeptidase (LAP), beta-galactosidase (GAL), leucocytes, erythrocytes, nitrite, protein (albumin), glucose, ketone, urobilinogen, bilirubin and pH were estimated in urine of rats after single (by gavage) or repeated (via drinking water) oral administration of diethylene glycol (DEG). Following single or repetitive doses (daily over 90 days) of 0.2 g DEG kg-1 body weight, no change in renal function was observed (no effect level). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These effects have also been confirmed in a myriad of species, including the mouse, rat, cat, pig and rabbit following oral or intraperitoneal exposure (Ballantyne and Snellings, 2005;Freundt and Weis, 1989;Herbert et al, 1978;Kraul et al, 1991;Mathews et al, 1991;Wiener and Richardson, 1989). Additionally, liver injury characterized by jaundice and moderate increases in liver enzymes has been reported in humans (Singh et al, 2001).…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…These effects have also been confirmed in a myriad of species, including the mouse, rat, cat, pig and rabbit following oral or intraperitoneal exposure (Ballantyne and Snellings, 2005;Freundt and Weis, 1989;Herbert et al, 1978;Kraul et al, 1991;Mathews et al, 1991;Wiener and Richardson, 1989). Additionally, liver injury characterized by jaundice and moderate increases in liver enzymes has been reported in humans (Singh et al, 2001).…”
mentioning
confidence: 71%
“…Normal, healthy rats exposed to a large single dose of DEG typically develop metabolic acidosis and acute renal failure (Kraul et al, 1991;Freundt and Weis, 1989). In this study, the model rats were less sensitive to the toxic effects of DEG compared with control rats in terms of the observed rats of metabolic acidosis and acute renal failure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although these studies demonstrated that metabolite accumulation was necessary for DEG toxicity (Besenhofer et al, 2010, 2011), EG (oxalate) accumulation was minimal and is now considered to be irrelevant for DEG toxicity. Although studies assessing the toxicity, pharmacokinetics, and biotransformation of DEG have been done using a variety of species including dogs, cats, mice, and rats (Winek et al, 1978; Lenk et al, 1989; Freundt and Weis, 1989; Wiener and Richardson, 1989; Mathews et al, 1991; Durand et al, 1976; Hebert at al., 1978; Harris, 1949), whether there is a sensitivity difference between Wistar and F-344 rats in renal toxicity or in DGA accumulation is yet unknown. Hence, this study was primarily designed to provide insight into an appropriate rat model by using a DEG dose response paradigm (0, 2, 5, or 10 g/kg) that covers the range of no to severe toxicity in Wistar rats (Besenhofer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%